Kegiatan Pengabdian kepada Masyarakat - Edukasi dan Skrining Kesehatan Pernapasan pada Kelompok Usia Remaja di SMA Kalam Kudus 2 - Susy Olivia Lontoh; Alexander Halim Santoso; Fidelia Alvianto; Muhammad Dzakwan Dwi Putra; Syilvia Cendy Enike; Valentino Gilbert Lumintang; Edwin Destra; Farell Christian Gunaidi (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Spirometry is a method for measuring lung capacity and function, playing a crucial role in the early detection of respiratory disorders. Among adolescents, education on respiratory health and spirometry examinations can help prevent respiratory issues that may impact quality of life. The objective of this community service activity was to enhance adolescents' understanding of the importance of maintaining respiratory health and to motivate them to adopt preventive measures. The methods employed included health education focusing on the risks of respiratory disorders and spirometry examinations for early detection. This program utilized the Plan-Do-Check-Act (PDCA) framework, encompassing planning, implementation of education and examinations, evaluation, and follow-up to improve the program. The results showed an increase in participants' understanding of risk factors and the benefits of spirometry examinations. Participants became more aware of the importance of maintaining respiratory health through healthy lifestyle practices. Health education and spirometry screening play a vital role in raising awareness and promoting preventive actions among adolescents concerning respiratory health. This activity is expected to serve as a foundation for similar programs focusing on respiratory health in adolescents.